Environmental assessment of an animal fat based biodiesel: Defining goal, scope and life cycle inventory - Vargas Ibáñez, Leidy T.; Cano Gómez, José J.; Zwolinski, Peggy; Evrard, Damien (2020)
The energy crisis and environmental problems have resulted in an increase of biofuels production. How- ever, the production cost is the biggest commercialization drawback for fuels such as biodiesel; the high- est cost in its production chain is associated with the raw material. Biodiesel is usually produced from vegetable oils; nevertheless, water supplies, fertilizers and large land areas are required for its produc- tion. An alternative is to use animal fat as the most economic raw material for biodiesel production. It does not compete with food safety and reduces the environmental impact caused by an inadequate dis- posal. But the use of biodiesel causes damages on some different parts of unmodified diesel engines and decrease their performance. Therefore, it is necessary to study additives that modify the thermodynamic and transport properties of biodiesel such as density, viscosity or surface tension. The aim of this research is to present the goal, scope and life cycle inventory necessary to evaluate the potential environmental impacts of ternary diesel + biodiesel + additives blends, as biofuels through life cycle assessment. Mass of reagents and blends components were identified, while they have already been tested and validated from the experimental data. The life cycle scenarios will include beef tallow, biodiesel, diesel and addi- tives production, mixing processes, and blends combustion.